PROGRAM PENGUATAN BUDAYA ORGANISASI ISLAMI PADA UNIT KEGIATAN MAHASISWA (UKM) PRAMUKA UNIVERSITAS MUHAMMADIYAH SURAKARTA - Arqy Ahmadi, Mirzam (STAI Terpadu Yogyakarta, 2023)
Organizational culture is a tool to unite various traits and characters in an organization which will become the identity of the organization. Organizational culture is very important to implement in an organization, both for employees and students. Various studies show that change management and organizational culture play an important role in creating good employee performance in an organization. This must be applied to organizations to support the smooth running and development of the organization, not only organizations and employees but also student organizations. The community service program through the capacity strengthening program (PPK) scheme is carried out with the